2004
DOI: 10.1080/02678370412331319794
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between bullying, psychosocial work environment and individual stress reactions

Abstract: It is frequently assumed that a poor psychosocial working environment will create conditions that encourage bullying. However, few studies have examined this assumption while comparing work environment ratings of bullied and non-bullied employees who work in the same organization and/or department. The objectives of this study were therefore, first, to investigate relationships between bullying and other psychosocial work environment factors within a particular organizational setting and, second, to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
227
3
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(256 citation statements)
references
References 32 publications
17
227
3
9
Order By: Relevance
“…Workload was assessed with one subscale of an adjusted and validated version of the Psychosocial Work Environment and Stress Questionnaire (PWSQ) (AGERVOLD & MIKKELSEN 2004;GUGLIELMI et al 2011). The scale included 5 items referring to the perception of the workload and job pressure (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Workload was assessed with one subscale of an adjusted and validated version of the Psychosocial Work Environment and Stress Questionnaire (PWSQ) (AGERVOLD & MIKKELSEN 2004;GUGLIELMI et al 2011). The scale included 5 items referring to the perception of the workload and job pressure (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Five items concerning psychological fatigue, work reluctance and mental preoccupation with work were used to assess mental fatigue (AGERVOLD & MIKKELSEN 2004). Mental fatigue was measured with a four-point frequency rating scale ranging from 1 ('never') to 4 ('always').…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies addressed poor leadership (2)(3)(4)(5)(6)(7)(8), three studies addressed personality (9)(10)(11), and 5 studies addressed gender and age (12)(13)(14)(15)(16). Two of these studies were qualitative studies.…”
Section: Risk Factors and Antecedent Of Bullying At The Workplacementioning
confidence: 99%
“…A total of 17 studies concerning risk factors and antecedents of bullying at the workplace were identified. Five of these studies addressed poor leadership (2;3;6;8;12) and management style (8), six studies addressed organizational climate (4;15;21;23) or organizational changes (5;7), two studies addressed conflicts at work (24) (22), two studies addressed personality (9;10) and two studies addressed gender and bullying at the workplace (13;14). Fifteen studies were crosssectional studies.…”
Section: Risk Factors In the Working Environmentmentioning
confidence: 99%